PENGARUH LINGKUNGAN KERJA DAN BEBAN KERJA, TERHADAP KEPUASAN KERJA MELALUI STRES KERJA PADA APARAT KEPOLISIAN DAERAH SUMATERA UTARA (STUDI PADA DIREKTORAT RESERSE KRIMINAL KHUSUS) - Emilan Siboro (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
The purpose of this study is to examine and analyze the effect of work environment and workload on job satisfaction through job stress at the North Sumatra Regional Police (Study at the Special Criminal Investigation Directorate) directly or indirectly. The approach used in this research is a causal approach. The population in this study were all North Sumatra Regional Police Officers at the Directorate of Special Criminal Investigation. The sample in this study used a saturated sample of 69 North Sumatra Police at the Special Criminal Investigation Directorate. Data collection techniques in this study used documentation, observation, and questionnaires. The data analysis technique in this study uses a quantitative approach using statistical analysis using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study uses the PLS (Partial Least Square) software program. The results of this study prove that work environment, workload and work stress have a significant effect on job satisfaction and indirectly work environment and workload have a significant effect on job satisfaction. Through job stress on the North Sumatra Regional Police